Sleep Disturbance is Associated With Higher Plasma Aβ Levels in Cognitively Normal Adults—A Population-Based Cross-Sectional Study - Gao, Yao; Wei, Shan; Gao, Fan; Gao, Ling; Dang, Liangjun; Shang, Suhang; Chen, Chen; Huo, Kang; Wang, Jingyi; Wang, Jin; Qu, Qiumin (Frontiers in Aging Neuroscience, 2021)
Objective: Growing evidence suggest that sleep disturbance is a risk factor for Alzheimer’s disease (AD). Amyloid-β (Aβ) deposition in the brain is a main pathophysiology of AD. Considering that peripheral Aβ level is associated with brain Aβ deposition, the present study investigated the relationship between sleep disturbance and plasma Aβ levels. Methods: This was a population-based cross-sectional study. A total of 1,459 participants from a village in the suburbs of Xi’an, China were enrolled from January 3 to March 26, 2017. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and good sleep quality defined as PSQI score <5 points, poor sleep quality defined as PSQI score >10. Cognitive function was assessed with the mini-mental state examination (MMSE). Fasting venous blood was taken in the morning and the plasma Aβ levels were measured using ELISA. The relationships between plasma Aβ levels and sleep quality was analyzed using multiple linear regressions. Results: Among 1,459 participants, 231 had poor sleep quality (15.83%). The log-transformed Aβ40 level had significant difference among different sleep groups (F=3.216, p=0.040). Log-transformed Aβ40 level was higher in poor sleep quality group than that in general sleep quality group [87.17 (73.42, 107.34) vs. 89.69 (74.81, 125.79) pg/ml, p=0.016]. In bivariate analysis, sleep quality was associated with plasma log-transformed Aβ40 level negatively (β=-0.025, p=0.011). Conclusion: In the community population, the poorer sleep quality is associated with higher plasma Aβ40 level. These indicated that sleep disturbance might also involve in peripheral Aβ clearance dysfunction.